Pendidikan dan Ilmu Pengetahuan Dalam Tradisi Islam Melayu - Eliza, Mita; Munir; Citra, Nia (Fakultas Adab dan Humaniora UIN Raden Fatah, 2024)
This research examines the significance of education and knowledge in the Malay Islamic tradition, emphasizing their role in personal growth, spiritual development, and societal progress. The study highlights the importance of seeking knowledge as urged by Prophet Muhammad and the integration of good manners (adab) in daily life. The qualitative descriptive approach is employed to explore the Islamic education system, the roles of pesantren (Islamic boarding schools) and madrasah (Islamic schools), and the contributions of notable Malay scholars. Findings indicate that Islamic education aims for holistic development, including moral and spiritual growth alongside academic knowledge. Pesantren play significant roles in religion, character building, cultural preservation, and social empowerment, while madrasah serve as centers of religious and ethical education. Key figures in Malay education reform are also discussed, showcasing their impact on educational advancement. This study underscores the interconnection between education, spirituality, and social responsibility within the Malay Islamic context.